Effect of overground locomotor training on ventilatory kinetics and rate of perceived exertion in persons with cervical motor-incomplete spinal cord injury - Panza, Gino S. (Spinal Cord Ser Cases, 2019)
STUDY DESIGN: Pre-post, pilot study. OBJECTIVES: To characterize ventilatory (V(E)) responses to exercise following warm-up walking in individuals with chronic incomplete spinal cord injury (iSCI) during constant work rate (CWR) exercise. Secondarily, to investigate V(E) and tidal volume (V(T)) variability, and ratings of perceived exertion (RPE) before and after overground locomotor training (OLT). SETTING: Research laboratory. METHODS: A 6-min CWR walking bout at preferred pace was used as a warm-up followed by 6 min of rest and a second 6-min CWR bout at above preferred walking pace. The second CWR bout was analyzed. Breath-by-breath ventilatory data were examined using a curvilinear least squares fitting procedure with a mono-exponential model. V(E) and V(T) variability was calculated as the difference between the observed and predicted values and RPE was taken every 2 min. RESULTS: Participants (n = 3, C4–C5) achieved a hyperpneic response to exercise in V(E) and V(T). OLT resulted in faster ventilatory kinetics and reductions of 24 and 29% for V(E) and V(T) variability, respectively. A 30% reduction in RPE was concurrent with the reductions in ventilatory variability. CONCLUSIONS: OLT may improve ventilatory control during CWR in patients with cervical motor-iSCI. These data suggest that in some participants with iSCI, ventilation may influence RPE during walking. Future research should investigate mechanisms of ventilatory variability and its implications in walking performance in patients with iSCI.